Evaluation of the feasibility and acceptability of the 'Care for Stroke' intervention in India, a smartphone-enabled, carer-supported, educational intervention for management of disability following stroke. Issue 2 (2nd February 2016) - Sureshkumar, K; Murthy, GVS; Natarajan, S; Naveen, C; Goenka, S; Kuper, H
Abstract : Objectives: (1) To identify operational issues encountered by study participants in using the 'Care for Stroke' intervention; (2) to evaluate the feasibility and acceptability of the intervention. Design: Mixed-methods research design. Setting: Participant's home. Participants were selected from a tertiary hospital in Chennai, South India. Participants: Sixty stroke survivors treated and discharged from the hospital, and their caregivers. Intervention: 'Care for Stroke' is a smartphone-enabled, educational intervention for management of physical disabilities following stroke. It is delivered through a web-based, smartphone-enabled application. It includes inputs from stroke rehabilitation experts in a digitised format. Methods: Evaluation of the intervention was completed in two phases. In the first phase, the preliminary intervention was field-tested with 30 stroke survivors for 2 weeks. In the second phase, the finalised intervention was provided to a further 30 stroke survivors to be used in their homes with support from their carers for 4 weeks. Primary and secondary outcome measures: Primary outcomes: (1) operational difficulties in using the intervention; (2) feasibility and acceptability of the intervention in an Indian setting. Disability and dependency were assessed as secondary outcomes. Results: Field-testing identified operational difficulties related to connectivity, video-streaming, picture clarity, quality of videos, and functionality of the application. The intervention was reviewed, revised and finalised before pilot-testing. Findings from the pilot-testing showed that the 'Care for Stroke' intervention was feasible and acceptable. Over 90% (n=27) of the study participants felt that the intervention was relevant, comprehensible and useful. Over 96% (n=29) of the stroke survivors and all the caregivers (100%, n=30) rated the intervention as excellent and very useful. These findings were supported by qualitative interviews. Conclusions: Evaluation indicated that the 'Care for Stroke' intervention was feasible and acceptable in an Indian context. An assessment of effectiveness is now warranted.